(untitled) (Pedagogy of Higher and Secondary Education, 2014)
Merzlykin P.V., Haradzhian N. A. The development of a typographic template for course project paper by means of cloud computing. The paper discusses the possibility of creating a typographic template for course project paper by means of cloud computing which should simplify the text formatting according to the requirements. The template may also be adapted for use in other higher education institutions and for formatting the text of graduation paper.